2013
DOI: 10.1007/s00442-013-2786-5
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of European lobster larvae (Homarus gammarus) to different quality food: effects of ontogenetic shifts and pre-feeding history

Abstract: Young larval stages of many organisms represent bottlenecks in the life-history of many species. The high mortality commonly observed in, for example, decapod larvae has often been linked to poor nutrition, with most studies focussing on food quantity. Here, we focus instead on the effects of quality and have investigated its effects on the nutritional condition of lobster larvae. We established a tri-trophic food chain consisting of the cryptophyte Rhodomonas salina, the calanoid copepod Acartia tonsa and lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 80 publications
3
22
0
Order By: Relevance
“…In trials of the so-called green water technique, utilizing algal cultures and enriched live feed more than doubled survival to the first post-larval instar compared with standard rearing protocols (Browne et al, 2009). The larval and post-larval stages are particularly vulnerable to the effects of nutrient limitation; therefore, nutritional enrichments improve growth and survival, even in standard culture environments (Daniels et al, 2010;Schoo et al, 2014). Further improvements have arisen from the long-awaited innovation of multilayered juvenile rearing systems, which increase hatchery capacity 40-fold compared with traditional single-layer vessels (Gowland, 2013).…”
Section: Improving Hatchery Productionmentioning
confidence: 99%
“…In trials of the so-called green water technique, utilizing algal cultures and enriched live feed more than doubled survival to the first post-larval instar compared with standard rearing protocols (Browne et al, 2009). The larval and post-larval stages are particularly vulnerable to the effects of nutrient limitation; therefore, nutritional enrichments improve growth and survival, even in standard culture environments (Daniels et al, 2010;Schoo et al, 2014). Further improvements have arisen from the long-awaited innovation of multilayered juvenile rearing systems, which increase hatchery capacity 40-fold compared with traditional single-layer vessels (Gowland, 2013).…”
Section: Improving Hatchery Productionmentioning
confidence: 99%
“…Nevertheless, this effect on carnivores varies according to species. In lobster larvae (Homarus gammarus), even subtle N and P limitations could cause negative effects on their growth conditions (Schoo et al 2014), whereas the condition of ctenophores Pleurobrachia pileus fed P-limited food sources was better than the condition of ctenophores in a nutrient-sufficient treatment, which was not expected . With regard to fish larvae, Malzahn et al (2007) observed that the food quality of primary producers significantly affected the condition of larval Baltic herring Clupea harengus, and a P-limited food chain resulted in significantly worse conditions compared with the N-limited and nutrient-sufficient food chain.…”
Section: Introductionmentioning
confidence: 83%
“…The ionic strength in the nutrient-limited treatments was maintained by the addition of KCl. Therefore, the algae of the 2 limitation treatments could only utilize the natural P or N sources present in the seawater, with the other nutrient added in excess, ensuring that the desired nutrient was limiting (Boersma et al 2009, Schoo et al 2014. Preliminary tests showed that nutrient composition (% of dry mass [DM]: %C, %N, and %P) and molar ratios (C:N, C:P, and N:P) of C. vulgaris (Table 1) changed significantly (all p < 0.05; Table 1) under the experimental conditions after a growth period of 5 d. Algae grown under the N-limited condition showed a lower value of N:P than the Full treatment (11.49 for −N and 27.54 for −F; Table 1), whereas the P-limited algae showed a higher value of N:P (71.58 for −P; Table 1).…”
Section: Primary Producermentioning
confidence: 99%
“…This increased growth may relate to the species composition with PQ showing the highest abundance in Saddle oyster A. ephippium, Peacock worm S. pavonina and Scallops Pectinidae, suggesting that these may be suitable food species. Species composition and quantity of feed are known to affect lobster growth (Schoo et al, 2012(Schoo et al, , 2014 and both spatial and temporal variations in plankton supply are well documented and monitored (SAHFOS, Sir Alister Hardy foundation for Ocean Science, 2015). Thus the availability of appropriate feed sources is an important factor for lobster development, which can account for these variations.…”
Section: Discussionmentioning
confidence: 99%